Dual-stage nanopositioning scheme for 10 Tbit/in2 hard disk drives with a shear-mode piezoelectric single-crystal microactuator - Zhang, L. (Institute of Electrical and Electronics Engineers Inc., 2016)
10.1109/TMAG.2014.2359417